Agricultural Transformation in Indonesia: Evaluation of Policy Implementation and Challenges Faced - Abdul Rahman (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This article aims to evaluate the implementation of agricultural policies and identify the challenges faced in the agricultural transformation process in Indonesia. The background of the study revolves around the importance of agricultural development in achieving sustainable economic growth, food security, and poverty reduction in the country. The study's objective is to assess the effectiveness of policy implementation and understand the key challenges hindering the agricultural transformation process. To achieve the research objective, a qualitative approach was employed. Qualitative interviews were conducted with key stakeholders, including government officials, farmers, and agricultural experts, to understand their perspectives on policy implementation and identify challenges faced at the ground level. The findings of the study reveal both positive outcomes and challenges in the implementation of agricultural policies in Indonesia. The policy implementation has led to increased investment in agricultural infrastructure, technology adoption, and productivity improvement in certain regions. However, challenges such as limited access to credit and markets, inadequate extension services, and climate change impacts have hindered the desired transformation. The study underscores the need for improved coordination between government agencies, increased investment in rural infrastructure, targeted support for smallholder farmers, and climate change adaptation strategies to overcome these challenges.